Pervaporation separation of isopropanol-water mixtures using crosslinked chitosan membranes - Mohd. Nawawi, Mohd. Ghazali; Hassan, Hashim (Penerbit UTM Press, 2003)
Chitosan membranes were prepared from local shrimp shells. Membranes were prepared as homogeneous (unmodified) and crosslinked chitosan. Chitosan membranes were modified via chemical crosslinking technique. The extent of crosslinking were determined by its crosslinking time. The pervaporation performances of the unmodified and the modified chitosan membranes were investigated in the pervaporation isopropanol-water systems. From the pervaporation experiments, it showed that chitosan membranes exhibited preferential permeation to water. The modified chitosan membranes showed a lower permeation flux but a higher separation factor than the unmodified membranes. The modified chitosan membrane had a better pervaporation performance than the unmodified membranes in terms of pervaporation separation index.